2015
DOI: 10.1016/j.combustflame.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation characteristics of gasoline direct-injection (GDI) engine soot: Catalytic effects of ash and modified kinetic correlation

Abstract: In this paper, experimental analyses are conducted into the GDI soot oxidation characteristics as dependent on engine operating conditions. Soot is sampled at various engine operating conditions of a commercial 2.4 L GDI engine with a naturally aspirated, homogeneous, and stoichiometric operation strategy. The oxidation reactivity, ash composition, and carbon nanostructure of the GDI soot samples are analyzed using thermogravimetric analysis (TGA), scanning electron microscope-energy-dispersive spectroscopy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 50 publications
2
38
0
6
Order By: Relevance
“…Also, soot oxidation reactivity was in good agreement with ash fraction in soot as described in 90 % soot oxidation time (T90) over ash fraction ( Fig. 2c), which validated our previous result [4]. This result may imply that low engine-out soot mass emissions from GDI engines contribute to enhanced soot oxidation due to high ash fraction in soot.…”
Section: Ash Impact On Gdi Soot Oxidation Reactivitysupporting
confidence: 89%
See 2 more Smart Citations
“…Also, soot oxidation reactivity was in good agreement with ash fraction in soot as described in 90 % soot oxidation time (T90) over ash fraction ( Fig. 2c), which validated our previous result [4]. This result may imply that low engine-out soot mass emissions from GDI engines contribute to enhanced soot oxidation due to high ash fraction in soot.…”
Section: Ash Impact On Gdi Soot Oxidation Reactivitysupporting
confidence: 89%
“…Previously the Ca-enhancing effect on soot oxidation was also observed [5,6,9,10], so this Ca-dominant ash formed during the combustion process seems to play a similar catalytic role in soot oxidation. This promoting effect of Ca-derived ash is assumed to be comparable to fuel-borne catalysts which lower oxidation temperatures [11,12]: our previous work from [4] indicates that oxidation temperatures appreciably decreased when ash content was high. Interestingly, the activation energy of soot oxidation was invariant with ash present, like Ce-additives [11].…”
Section: Investigation Of Soot Oxidation Reactivitymentioning
confidence: 95%
See 1 more Smart Citation
“…Although this surrogate soot has low contents of volatile compounds and ash [17,18], compared with engine soot, our other studies showed that the former has crystalline structure almost identical to GDI soot. Its partially oxidized samples were prepared in a thermogravimetric analyzer (TGA) as below.…”
Section: Sample Preparationmentioning
confidence: 89%
“…Aus der Literatur ist bekannt, dass das Vorhandensein geringer Mengen von Metalloxiden oder nichtoxidischen Mineralien die Rußoxidation katalysieren können [11], [19]. XPS-Untersuchungen von Ascherückständen der untersuchten Pulverproben zeigen unter anderem signifikante Anteile von Na, Ca, Zn, Si, die hautpsächlich von Schmieröl-Additiven stammen.…”
Section: Tga-ftir Der Pulverprobenunclassified